Penanganan Lahan Kritis dengan Metode Konservasi Lahan di Citarum Hulu - Marenda Ishak Sonjaya Sule; Shantosa Yudha Siswanto; Nadia Astriani (Universitas Mathla'ul Anwar Banten, 2021)
LAND CRITICALY HANDLING USING CONSERVATION METHODS ON UPPER CITARUM. The annual loss of erosion in Java is Rp. 5.9 trillion (Kompas, 21 October 2020). This illustrates, we are so weak in the aspects of planning, development, and supervision. One of the problems experienced in the upper of Citarum river is the level of erosion reach 120 tons/ha/ year (Risdiyanto, 2009). According to Hardjowigeno (1986), the erosion limit that can be tolerated is generally around 20 tonnes /ha/year. Seeing this condition, the problem of erosion is an important thing for community assistance. Community service aims to conduct training, mentoring, and field trials to reduce the rate of erosion. This service is carried out to farmer groups at Cimenyan District. The result of this service activity is the formation of awareness for agricultural business actors. Second, the allocation of proceeds from efforts to prevent erosion and sedimentation. Third, erosion can be maximally reduced, characterized by existing demonstration plots.